Early childhood math routines : empowering young minds to think - Cameron, Antonia (Stenhouse Publishers, 2020)
"This book begins by pushing back on the kind of rote routines that lack opportunities for reasoning (like the calendar) that teachers often use in early childhood and primary classrooms. Instead, the author offers innovations on old routines and some new routines that encourage reasoning, argumentation, and the development of important math ideas. She focuses on using math routines in playful ways with your children. See chapter titles for the different routines featured in the book"--